Prevalence and Pattern of Hypodontia among Croatian Orthodontic Patients - Daša Nikolov Borić; Zorica Radalj Miličić; Anita Kranjčević Bubica; Senka Meštrović (University of Zagreb. School of Dental Medicine, 2020)
Objective: The objective of this retrospective study was to assess the prevalence of hypodontia in the permanent dentition among Croatian orthodontic patients. The occurrence was evaluated concern-ing gender, specific missing teeth, the location, pattern of distribution in the maxillary and mandibu-lar arches and sagittal and vertical skeletal pattern. Material and Methods: The sample consisted of 194 patients (75 males and 119 females) from the Department of Orthodontics, Dental Clinic, Clinical Hospital Center Zagreb. Based on the severity of hypodontia the sample was divided into mild (1-2 missing teeth), moderate (3-5 missing teeth) and severe groups (6 or more missing teeth). The location of missing teeth was used to further divide the sample into anterior (intercanine region), posterior (premolars and molars) and anteroposterior groups. In addition, jaw localization of hypodontia was also considered. Results: Permanent dentition hypodontia among Croatian orthodontic patients was found to be generally mild (80%), and a distribution was similar in the maxilla (39%) and the mandible (41%), as well as in the anterior and posterior segments of dental arch 44%). The number of missing teeth per person ranged from 1 to 12, with no significant difference between genders. The severity and location of hypodontia did not differ significantly between the genders, as well as in be-tween the categories of sagittal and vertical skeletal patterns. Conclusion: Present results suggest that the treatment plan for patients with hypodontia in permanent dentition should be individualized and adjusted for each case.